Risk factors of dementia in type 2 diabetes mellitus: The Hong Kong diabetes study - Yau-Lam Alex Chau; Ji Won Yoo; Jiandong Zhou; Cosmos LiutaoGuo; Wing Tak Wong; Carlin Chang; Tong Liu; Kamalan Jeevaratnam; Qingpeng Zhang; Gary Tse; Sharen Lee (Aging and Health Research, 2023)
This population-based cohort study investigated the risk factors of incident dementia and vascular dementia in type 2 diabetic patients (≥45 years old) attending the Hong Kong Hospital Authority between 1st January and 31st December 2009.Of the 273,876 patients included,9994 showed incident dementia (median follow-up: 4245 days). Multivariable Cox regression identified older age (HR: 1.09 [95% CI: 1.08–1.10]) and antiplatelet use (HR: 1.36 [1.14–1.62]) as risk factors for incident dementia, and older age (HR: 1.07 [1.06–1.08]), ischemic stroke (HR: 1.47 [1.09–1.98]), fasting blood glucose (HR: 1.10 [1.01–1.20]), antiplatelets (HR: 1.92 [1.51–2.44]), and calcium channel blocker (HR: 1.28 [1.04–1.57]) use as risk factors of incident vascular dementia.